Can a High Reloading Dose of Atorvastatin Prior to Percutaneous Coronary Intervention Reduce Periprocedural Myocardial Infarction?. (March 2014) - Nafasi, Latifeh; Rahmani, Reza; Shafiee, Akbar; Salari, Arsalan; Abdollahi, Alireza; Meysamie, Alipasha
Abstract Background: Periprocedural myocardial infarction (MI) is a common complication following percutaneous coronary intervention (PCI) and statins have been shown to reduce MI in statin-naïve patients. We aimed to identify whether a high reloading dose of atorvastatin can prevent MI following PCI in patients who were already being treated with statins. Material and methods: In this triple-blind controlled randomized clinical trial, 190 candidates for elective PCI, who were already using statins and/or other lipid lowering agents such as fibrates, were randomly assigned to two equal groups to receive either atorvastatin (80 mg) or placebo within 24 hours before the procedure. Serum levels of creatinine kinase myocardial isoenzyme (CK-MB), cardiac troponin I (cTNI) and high-sensitive C-reactive protein (hs-CRP) were measured at baseline and then 6 and 12 hours following PCI. Post-procedural MI was defined as troponin elevation >5-fold in patients with normal baseline or >20% in those with elevated baseline measurements with or without chest pain or ST segment or T wave abnormalities. Results: Frequency of MI in the atorvastatin group was 3 (3.1%) vs. 10 (10.5%) in the placebo group (p = 0.04). The CK-MB rise within 6 hours following PCI was 0.6 ± 0.3 mg/dl in the intervention group versus 3.0 ± 1.6 mg/dl in the placebo group. Also, the levels of cTNI within 6 and 12 hours in the intervention group was significantly lower than the placebo group (p = 0.01 and 0.008, respectively). hs-CRP was significantly lower in the intervention group after 12 hours (p = 0.004). Conclusion: Administration of a high reloading dose of atorvastatin within 24 hours before PCI could significantly reduce the frequency of periprocedural MI. Clinical trial registration code: IRCT201205209768N1.